Characterization of social behavior in young and middle-aged ChAT-IRES-Cre mouse - Lhopitallier Cyrill; Perrault Charlotte; Chauveau Frederic; Saurini Francoise; Berrard Sylvie; Granon Sylvie; Faure Alexis (Public Library of Science, 2022)
The cholinergic system is an important modulator of brain processes. It contributes to the regulation of several cognitive functions and emotional states, hence altering behaviors. Previous works showed that cholinergic (nicotinic) receptors of the prefrontal cortex are needed for adapted social behaviors. However, these data were obtained in mutant mice that also present alterations of several neurotransmitter systems, in addition to the cholinergic system. ChAT-IRES-Cre mice, that express the Cre recombinase specifically in cholinergic neurons, are useful tools to investigate the role of the cholinergic circuits in behavior. However, their own behavioral phenotype has not yet been fully characterized, in particular social behavior. In addition, the consequences of aging on the cholinergic system of ChAT-IRES-Cre mice has never been studied, despite the fact that aging is known to compromise the cholinergic system efficiency. The aim of the current study was thus to characterize the social phenotype of ChAT-IRES-Cre mice both at young (2–3 months) and middle (10–11 months) ages. Our results reveal an alteration of the cholinergic system, evidenced by a decrease of ChAT, CHT and VAChT gene expression in the striatum of the mice, that was accompanied by mild social disturbances and a tendency towards anxiety. Aging decreased social dominance, without being amplified by the cholinergic alterations. Altogether, this study shows that ChAT-IRES-Cre mice are useful models for studying the cholinergic system‘s role in social behavior using appropriate modulating technics (optogenetic or DREADD).